Participatory Research Ethics - Aruskipt’asipxaňanakasakipunirakispawa - Eisenberg, Amy (Ethnobotany Research and Applications, 2018)
Collaborative ethnographic research with First Nations Peoples contributes to our understanding of humanity, its dynamic processes, and possibilities toward sustainable ways of living in harmony with Mother Earth. Cultural diversity is one of the greatest gifts bestowed on humanity (Spradley 1979:v). When conducting participative research with indigenous peoples, it is essential for the fieldworker to adopt a holistic perspective with the awareness that ethnographic interviewing is a cross-cultural opportunity of intimate communication, exchange and fellowship. The researcher must be conscious of her/his personal biases and assumptions that directly reflect their ethics and values, as well as the research process and outcomes.